2014
DOI: 10.1111/aas.12309
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human growth hormone improves cognitive capacity in a pain patient exposed to chronic opioids

Abstract: During recent decades, the increasing use of opioids for chronic non-cancer pain has raised concerns regarding tolerance, addiction, and importantly cognitive dysfunction. Current research suggests that the somatotrophic axis could play an important role in cognitive function. Administration of growth hormone (GH) to GH-deficient humans and experimental animals has been shown to result in significant improvements in cognitive capacity. In this report, a patient with cognitive disabilities resulting from chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Although future studies would be needed to confirm, this may suggest that the link to IGF-1 levels and the effectiveness of a GH therapy may be specific to widespread muscle pain disorders in adults and not neonatal inflammatory pain states. Nevertheless, our results show GH has profound effects on injury responses during postnatal development, suggesting that a short course of low dose GH replacement therapy may eventually be used as an effective pharmacological treatment strategy for neonatal pain that does not cause unwanted side effects typically seen with extended GH delivery in humans [2,53]. As neonatal injury is known to alter primary afferent function [24] which can reorganize the developing DH if initiated at early ages [68], this strategy may also mitigate the long-term consequences of early life insult on adult nociceptive processing [14,68].…”
Section: Discussionmentioning
confidence: 99%
“…Although future studies would be needed to confirm, this may suggest that the link to IGF-1 levels and the effectiveness of a GH therapy may be specific to widespread muscle pain disorders in adults and not neonatal inflammatory pain states. Nevertheless, our results show GH has profound effects on injury responses during postnatal development, suggesting that a short course of low dose GH replacement therapy may eventually be used as an effective pharmacological treatment strategy for neonatal pain that does not cause unwanted side effects typically seen with extended GH delivery in humans [2,53]. As neonatal injury is known to alter primary afferent function [24] which can reorganize the developing DH if initiated at early ages [68], this strategy may also mitigate the long-term consequences of early life insult on adult nociceptive processing [14,68].…”
Section: Discussionmentioning
confidence: 99%
“…According to this evidence, it is likely that GH may facilitate the proliferation, differentiation and survival of new neurons in response to brain injury. To date, only few studies in humans explore such a possibility indicating a positive effect for GH treatment together with specific neurorehabilitation [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]; but all patients in these studies had GH deficiency, and only one study [ 8 ] describes that GH administration, together with rehabilitation, may be useful for the recovery of TBI patients without GHD.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that GH and insulin-like growth factor 1 (IGF-I) play a role on brain repair after an injury was postulated years ago [ 16 , 17 , 18 , 19 ], and a number of studies from our group and others demonstrated this, both in GH-deficient (GHD) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] and non-GHD [ 8 , 29 ] patients with acquired brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Brain damage provoked during delivery was treated with GH in a 10-year-old girl, resulting in a significant improvement in cognitive function [ 117 ]. In patients treated with opioids, GH improved hippocampal cognitive function [ 118 ]. This beneficial effect likely involves the downregulation of NMDA receptors and the prevention of opioid-related excitotoxicity [ 64 ].…”
Section: Expression and Neurotrophic Effects Of Growth Hormone (Ghmentioning
confidence: 99%